Comparison of Hemodynamic Stability and Adverse Effects of Carbetocin versus Oxytocin During Cesarean Delivery (Journal of Rangpur Medical College, 2026)
Background: Postpartum hemorrhage is a significant cause of maternal morbidity, and optimizing uterotonic use during cesarean delivery is critical. Objective: This study compared hemodynamic stability and the adverse effects of carbetocin versus oxytocin. Methods: An observational study was conducted in the Department of Obstetrics and Gynaecology at BGC Trust Medical College Hospital, Chittagong, Bangladesh, over six months from January to June 2022 among 100 women undergoing cesarean section, divided into a carbetocin group (100 μg IV bolus) and an oxytocin group (10 IU IV infusion). Hemodynamic changes, estimated blood loss, need for additional uterotonics, and adverse effects were evaluated. Results: Baseline characteristics were similar across groups. Mean blood loss was lower with carbetocin (630±225 mL) than oxytocin (685±267 mL), though not statistically significant. Additional uterotonics were required less frequently with carbetocin (12% versus 28%). Adverse effects were mild and comparable, with no serious complications. Conclusion: Carbetocin provides hemodynamic stability and reduces the need for additional uterotonics, making it an effective alternative to oxytocin, especially in resource-limited settings.J Rang Med Col.2026 Mar;11(1): 39-44